Efficacy of Silicone Gel versus Silicone Gel Sheet in Hypertrophic Scar Prevention of Deep Hand Burn Patients with Skin Graft: A Prospective Randomized Controlled Trial and Systematic Review. Issue 10 (October 2020) - Pruksapong, Chatchai; Burusapat, Chairat; Hongkarnjanakul, Natthawoot
Abstract : Background: Burn injuries are burdensome to the public health system. Hypertrophic scars are the most common undesirable sequelae associated with burn scar contracture, resulting in reduced hand function. This study compared 2 different forms of silicone combined with pressure garment (PG) to determine the efficacy in hypertrophic scar prevention in hand burns. Methods: A systematic review was also performed, including only randomized control trials with silicone materials in burned patients. A prospective intraindividual randomized controlled trial was conducted to compare the efficacy of 3 treatment groups: silicone gel and silicone gel sheet combined with PG versus PG alone. Results: There were no significant differences in all Vancouver Scar Scale parameters. Three of 6 Patient and Observer Scar Assessment Score parameters showed significant differences among the 3 groups ( P < 0.05). Scar stiffness improved at 8- and 12-weeks follow-up in both silicone gel and silicone gel sheet combined with PG; however, there was no significant difference between silicone groups. Scar thickness significantly improved at 2, 4, and 8 weeks in the silicone gel group compared with PG. Scar irregularity significantly improved at 2, 4, 8, 16, and 20 weeks in both silicone combined PG groups compared with PG alone. Conclusions: Silicone gel and silicone gel sheet combined with PG were more effective than PG alone in some aspects of the Patient and Observer Scar Assessment Score. However, there was no significant difference between the silicone gel and silicone gel sheet on the Vancouver Scar Scale.